Analyzing the risk of cyberattacks on pharmacy information systems - Agrawal, Ashish; Chandrakar, Kunal (Journal of Neonatal Surgery, 2025)
As the world moves closer to a cashless and paperless economy, digitization is essential for any firm to succeed. Although initiatives to encourage digitization have been started, cyber risk was overlooked, and the danger of cyberattacks has been rising and is far more than the perceived risk of cyber. Globally, there has been a startling rise in cyberattacks of all kinds, which have in certain cases caused some businesses to become unstable and taken days or months to recover. In addition to the other operational problems, the recovery period resulted in cost and market share loss. This study aimed to determine the factors that influence an individual's readiness to manage cyber risks by examining the role of respondents' online behavior, awareness of cyber risks, experience with cyber risks, and attitude toward cyber risks in lowering the incidence of cyber risks. 385 respondents were given a structured questionnaire by the researcher, and the information gathered was coded and revised for additional analysis. The data was subjected to univariate, bivariate, and multivariate analysis, and the researcher employed regression, t-test, and Anuva to highlight the study's framework. The findings show that an individual's online behavior and awareness of cyber hazards contribute to their readiness to manage those risks. An individual will be able to improve their readiness to manage cyber hazards with the help of the findings